2017
DOI: 10.1021/acs.iecr.7b00255
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Partial Oxidation of Iso-octane over Rh/α-Al2O3 in an Adiabatic Reactor: An Experimental and Modeling Study

Abstract: Catalytic partial oxidation (CPO) of hydrocarbons represents an interesting technology for hydrogen production on mobile systems. We investigated the CPO of 2,2,4-trimethyl pentane (iso-octane), chosen as surrogate for gasoline. CPO experiments were carried out in a laboratory scale autothermal reformer with honeycomb monolith catalysts (2% Rh/α-Al 2 O 3 ), equipped with probes for spatially resolved measurements of temperature and concentration. The iso-octane CPO process follows a reaction pathway which main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The largest difference occurs between the inlet and midpoint of the catalyst, suggesting that this is the area of most interest. This is in agreement with observations by Carrera et al, who found that, during catalytic partial oxidation experiments with iso-octane over a Rh/Al 2 O 3 catalyst, a hot spot has a tendency to form near the catalyst inlet before the formation of water and subsequent steam reforming processes lowered the catalyst temperature further downstream ,moving toward the catalyst exit . Comparing the midpoint and outlet temperatures for all three cases in Figure , the temperature decreases by roughly the same amount regardless of O/C ratio and reformate yields.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The largest difference occurs between the inlet and midpoint of the catalyst, suggesting that this is the area of most interest. This is in agreement with observations by Carrera et al, who found that, during catalytic partial oxidation experiments with iso-octane over a Rh/Al 2 O 3 catalyst, a hot spot has a tendency to form near the catalyst inlet before the formation of water and subsequent steam reforming processes lowered the catalyst temperature further downstream ,moving toward the catalyst exit . Comparing the midpoint and outlet temperatures for all three cases in Figure , the temperature decreases by roughly the same amount regardless of O/C ratio and reformate yields.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Unfortunately, partial oxidation reforming alone is exothermic, meaning a portion of fuel energy is lost as heat during reforming. , This reforming process is also less efficient at hydrogen production from a fuel usage standpoint, producing a much smaller number of moles of hydrogen per mole of fuel burned. However, in an environment where both oxygen and water vapor are present, both types of reforming can occur simultaneously. , Heat generated by the exothermic partial oxidation reactions can drive endothermic steam reforming. , Thus, the net energy balance of the total reforming process is highly dependent on the availability of both oxygen and heat in the system. Achieving optimal engine efficiency using this strategy requires a balance that achieves adequate hydrogen production without losing excessive energy as heat during reforming.…”
Section: Introductionmentioning
confidence: 99%
“…Such an unbalancing of exothermic and endothermic contributions is fuel-specific, being related to the slow diffusivity of i-C8, which enhances the consecutive nature of the surface process [2], and to its high gas phase reactivity, which results in the onset of homogeneous reactions upon an ignition delay. The onset of gas phase reactions is progressively shifted downstream on increasing the flow rate, as evidenced by the change of slope of iC8 conversion curves in Figure 6.…”
Section: Modeling Analysismentioning
confidence: 99%
“…According to IEA, the transportation sector ranks at the second position in terms of energy consumption and projections show that, in the 2015-2040 period, its demand for energy will grow more quickly than the industrial field, reaching 1%/year, 0.3% higher than the industrial rate [1]. To supply this ever-increasing demand, while coping with the commitment to mitigating CO 2 emissions, fuel cell and hydrogen technology can be a key player [2,3]. The final goal of a green energy market is the full exploitation of renewable energy sources (with H 2 production via water electrolysis); however, the development of a decentralized H 2 -production and supply chain based on small scale processors represents a realistic transition strategy [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation